Who becomes an entrepreneur after university? Evidence from Canada - Creso Sá; Summer Cowley; Aisha Husain (PLoS ONE, 2025)
In recent decades there has been significant interest among policy makers in supporting entrepreneurship among university students, with the goal to improve labor market outcomes and contribute to the economy through venture creation. Drawing from the 2018 National Graduate Survey in Canada, our study examines who engages in entrepreneurial activity after graduation, investigating differences among demographic groups and between those who participated in entrepreneurship education on campus and those who did not participate. We find that those graduates who participated in entrepreneurship education are more likely to be self-employed and own their own business three years after graduating than the general population of university graduates. We also find differences according to gender, citizenship, and socio-economic status in entrepreneurial activity. Our results are consistent with previous studies documenting demographic disparities in entrepreneurship and provide more generalizable evidence about the relationship between entrepreneurship education and subsequent entrepreneurship.